Development and Evaluation of a Dynamic Response Cognitive Interview Methodology for Nutrition Education Material Design (P13-010-19). (13th June 2019) - Eck, Kaitlyn; Delaney, Colleen; Olfert, Melissa; Shelnutt, Karla; Byrd-Bredbenner, Carol
Abstract: Objectives: Cognitive testing (CT), an underutilized methodology in nutrition education, is applied during the development of educational materials to gauge the target audience's comprehension and interest in the education material's content as well as to assess whether the presentation (e.g., wording, design) of the content is responsive to the audience's sensibilities. CT data elucidate areas needing refinement to increase the effectiveness and acceptability of educational materials. Typically, CT interviews are conducted with ∼12 individuals from the target audience before data are content analyzed and used to refine materials. Waiting to revise materials until all CT interviews are completed often necessitates additional interviews to determine if the revisions sufficiently addressed areas needing refinement. To overcome the methodological inefficiency of typical CT, our lab developed and tested the feasibility of using a dynamic response CT (DRCT) methodology that iteratively refined materials after every CT interview. Methods: The materials tested using DRCT interviews were designed to enable parents of school-age children to develop knowledge, skills, and self-efficacy for shaping home environments and lifestyle practices to prevent childhood obesity. Eight sets of materials were tested in 3 states (NJ, WV, FL). DRCT interviews were conducted by two trained nutrition researchers: one conducted the interview using a semi-structured script and the other took detailed notes. Within 24 hours of each DRCT interview, the notes were submitted for content analysis by two researchers who collaboratively used the analysis to revise the materials within 48 hours of interview completion and before the materials were tested again. The revised materials underwent DRCT again, and the revision process was repeated until data saturation was reached. Results: DRCT interviews were conducted with 71 parents (90% female). Data saturation was reached with an average of 10 interviews. Conclusions: The DRCT methodology requires constant availability of researchers to content analyze data and refine materials to ensure readiness for subsequent interviews. However, it compresses the timeline for data collection thereby saving research costs and getting tested educational materials to the target audience faster. Funding Sources: 2011–68, 001-30, 170 and 2017–680, 001-26, 351.